2019
DOI: 10.17305/bjbms.2019.4297
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 may be a prognostic biomarker in IDH1/2 wild-type primary glioblastomas

Abstract: Primary glioblastoma (GB) is the most aggressive type of brain tumors. While mutations in isocitrate dehydrogenase (IDH) genes are frequent in secondary GBs and correlate with a better prognosis, most primary GBs are IDH wild-type. Recent studies have shown that the long noncoding RNA metastasis associated lung adenocarcinoma transcript-1 (MALAT1) is associated with aggressive tumor phenotypes in different cancers. Our aim was to clarify the prognostic significance of MALAT1 in IDH1/2 wild-type primary GB tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In their study, they found that upregulation of MALAT1 expression was associated with shorter survival rate in IDH1/2 wild-type primary glioblastoma patients, and overexpressed MALAT1 was associated with younger age and left-sided glioblastoma localization. In addition, they also reported that MALAT1 expression substantially increased in the insular lobe relative to other lobes [ 74 ]. This indicates that MALAT1 might be regard as a potential biomarker and therapeutic target in primary glioblastoma patients.…”
Section: Overview Of Long Non-coding Rnas In Glioblastomamentioning
confidence: 99%
“…In their study, they found that upregulation of MALAT1 expression was associated with shorter survival rate in IDH1/2 wild-type primary glioblastoma patients, and overexpressed MALAT1 was associated with younger age and left-sided glioblastoma localization. In addition, they also reported that MALAT1 expression substantially increased in the insular lobe relative to other lobes [ 74 ]. This indicates that MALAT1 might be regard as a potential biomarker and therapeutic target in primary glioblastoma patients.…”
Section: Overview Of Long Non-coding Rnas In Glioblastomamentioning
confidence: 99%
“…TSIX transcript, XIST antisense RNA (TSIX) is considered to orchestrate the initiation of X chromosome inactivation, thus determining which X chromosome remains active by blocking the expression of the antisense XIST RNA (27). Another lncRNA, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), was originally identified as a prognostic marker for metastatic lung cancer (28); however, it is also associated with several other human tumors, such as HCC (29) and glioblastoma (30). Therefore, the current study aimed to identify potential ncRNAs regulating PD-L1 expression in TNBC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is traditionally the most investigated epigenetic modification [ 8 ], and it can be experimentally identified in liquid biopsies. Abnormal DNA methylation may be classified as hyper- or hypomethylation.…”
Section: Introductionmentioning
confidence: 99%